Niepomijalność administracji publicznej w zakresie władztwa zakładowego — „skreślenie z listy uczniów szkoły” na kanwie orzecznictwa sądowoadministracyjnego - Raszewska-Skałecka, Renata (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The subject matter of procedures in the individual cases of a student, including administrative establishment’s power towards a student on school territory and removal from the list of students, affects students’ status as so-called users of administrative establishments and is not only relevant and present in administrative law, but still needs the courtsʼ verification and scientific reflection in practice. The procedure for removing a student from the list of students is pending under theprovisions of administrative procedural law. A student is removed from the list of students on the basis of the administrative decision and is tantamount to the cessation of the administrative-legal relationship between a student and school. It has to be underlined that a student has the obligation to obey internal regulations which are passed in the school and which are binding on its premises. In particular, these regulations include the school statute. Powers of an administrative establishment (school) towards a student — the so-called “user” — are usually statutorily prescribed and clearly specified in the school statue and in internal school regulations. In the doctrine of administrative law, it is considered that the subordination of a student as a user of the administrative establishment is regulated in education law and his subordination to other acts and orders of the school authorities is defined as an element of the administrative establishment’s power. Hence, there is a presence and unavoidability of legal forms of public administration activity in the school and administrative establishment’s power influencing the legal situation of a student in the school. Administrative law allows for taking a view on the legal protection of a student and administrative court judiciary allows for taking a view on the legal protection of public subjective rights of an individual — a student in the state ruled by law.
Keywords: the right to education; schooling duty and education’s duty; education law; administrative establishment; administrative establishment’s power; school statute; removal from the list of students